An SIR Model for COVID-19 Outbreak in India - Sweatha, S.; Monisha, P.; Devi, S. Sindu (Communications in Mathematics and Applications, 2022)
In this paper, we have proposed a SIR fuzzy epidemic model by taking the transmission rate and recovery rate as fuzzy numbers. The basic reproduction number and the fuzzy basic reproduction number have been computed. Further by considering the initial values for the susceptible, infected and recovered population the numerical simulation has been carried out using Runge-Kutta method. We can predict the transmission of the virus and prevent the COVID-19 outbreak in India with the results obtained from the proposed SIR model.
Keywords: Reproduction number; Fuzzy basic reproduction number; Runge-Kutta method